Improving Employee Performance: The Roles Of Work Environment, Work Motivation And Work Discipline - Rulianti, Erina; Nurpribadi, Giri (Lentera Ilmu Nusantara, 2024)
The issue of employee performance remains highly relevant in supporting a company's operational activities. Therefore, many companies strive to enhance their employees' performance to achieve organizational success. This research aims to examine the influence of the work environment, work motivation, and work discipline on the performance of PT Katolec Indonesia employees. The sampling method used was a saturated non-probability sampling technique, ensuring that the entire population of 70 employees, including 63 production staff, 4 leaders, and 3 quality control personnel, was included in the sample. This study employs a quantitative approach, with data collected through questionnaires filled out by PT Katolec Indonesia employees. The analysis methods used include the Validity Test, Reliability Test, Classical Assumption Test, Regression Test, and Hypothesis Testing, conducted using the IBM SPSS 23 for Windows program. The research findings indicate that the work environment, work motivation, and work discipline significantly influence employee performance. The practical implications of this study suggest that companies should focus on improving workplace conditions, fostering employee motivation, and enforcing work discipline to enhance overall employee performance and achieve organizational goals effectively.